Prevalence of golf-related injuries among recreational golfers in Malaysia / Hanis Haziqah Roslan ... [et al.] - Roslan, Hanis Haziqah; Danis, Ajau; Masuri, Mohamad Ghazali; Md Isa, Khairil Anuar (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Golf is a non-contact sport that requires a complex movement involving the entire body to execute an efficient swing. As the movement is repeatedly made, it increases the pressure on the body structures such as muscles, joints, nerves, and tendons. Consequently, this will increase the risk of injuries during golf games. This study aimed to determine the prevalence and anatomical distribution of injury among recreational golfers. Several golf clubs in Selangor, Malaysia, were chosen as study settings due to their popularity among golfers in Malaysia. An online retrospective cross-sectional study design was used. Data were analyzed by using SPSS 22.0 and descriptively described. A total of 372 recreational golfers participated in the survey. Statistically, 98.9% of the respondents were male, with 87.4% being 40 years and above. Meanwhile, for Body Mass Index (BMI), 60.0% were overweight and obese. The prevalence of golf-related injuries was 51.1%, with 80.5% of injuries sustained during playing at the golf course. Anatomically, it was the upper extremities that comprised 53.3% of the total injury. The type of injuries in the upper extremity included shoulder muscle strain (77%), golfer’s elbow (63%), wrist sprain (57%), and shoulder sprain (51%). Significantly, there is an association between golfing frequency and golf-related injuries (p < 0.05). In conclusion, there was a significantly higher prevalence of injuries among golfers. Further study is warranted to establish the effect of injury on golfers’ performance and quality of life.